ANALISIS TINGKAT KEPATUHAN WAJIB PAJAK (WP) ATAS PENYAMPAIAN SURAT PEMBERITAHUAN (SPT) TAHUNAN PPH ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA PONTIANAK - B51111118, Mardyana (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This research aimed to find out the level of tax compliance in submitting the annual Letter (SPT) Personal Income Tax, and to identify factors that cause the Tax Office to fail to reach the targeted tax and what the Office has done to increase the level of tax compliance. This study used qualitative descriptive type of research. It was a case study on the Pratama Tax Office Pontianak. The results showed that the level of tax compliance in 2014 was below the target i.e 62.48% of the total number of taxpayers re           quired to submit their SPT. The figure was in fact far from the target set which was 65.00% of the compliance ratio target as it was set too high compared to other KPP. A lack of socialization provided by the Pratama Tax Office Pontianak to taxpayers also seriously influenced the level of compliance. This can be seen in the report on the achievement of comliance ratio in the submission of the Annual Letter (SPT) of Personal Income Tax in the period of 2011-2014.   Keywords: Level of Compliance, Tax, Realization of Target Achievement